Challenges and Recent Advances in Medulloblastoma Therapy. (December 2017) - Kumar, Vinod; Kumar, Virender; McGuire, Timothy; Coulter, Donald W.; Sharp, John G.; Mahato, Ram I.
Abstract : Medulloblastoma (MB) is the most common childhood brain tumor, which occurs in the posterior fossa. MB tumors are highly heterogeneous and have diverse genetic make-ups, with differential microRNA (miRNA) expression profiles and variable prognoses. MB can be classified into four subgroups, each with different origins, pathogenesis, and potential therapeutic targets. miRNA and small-molecule targeted therapies have emerged as a potential new therapeutic paradigm in MB treatment. However, the development of chemoresistance due to surviving cancer stem cells and dysregulation of miRNAs remains a challenge. Combination therapies using multiple drugs and miRNAs could be effective approaches. In this review we discuss various MB subtypes, barriers, and novel therapeutic options which may be less toxic than current standard treatments. Trends: Medulloblastoma accounts for 15–20% of all pediatric brain tumor and is a leading cause of cancer-related deaths in children. The latest classification categorizes medulloblastoma into four subtypes – Wnt, Shh, group 3, and group 4 – based on signaling pathways and whole-genome sequence analysis. Chemoresistance caused by stem cells, miRNA dysregulation, and the blood–brain barrier is the main obstacle in medulloblastoma therapy. Polymeric nanomedicines carrying small-molecule inhibitors and miRNA have potential to cross the blood–brain barrier and treat the disease effectively.